Effect of Financial Liberalization on Real Estate Prices in Kenya - Kakoko, Reuben C. (University of Embu, 2020)
The study established the impact of financial liberalization of real estate prices in Kenya. The study established the effect of central bank rates, commercial bank lending rates and inflation rates on real estate prices in Kenya .the study followed a descriptive research design and used secondary data. The study used average annual secondary data for period between 2006 to 2019. The independent variables CBR, interest rates and inflation rates were obtained from CBK websites, while the real estates were obtained from Centum consult .the study used excel spread sheet to organize the data SPSS version 24 to analyses the data .the study establish that study variables fluctuated throughout the period. The real estates prices grew each year since 2016 to 2019. Regression analysis results reviewed that there is a strong positive relationship between the independent variables (CBR, commercial bank lending rates and inflation rates).The concludes that a change in CBR cause the highest influence on real estates prices followed inflation rates. The study recommends that regulators and policy makers should uphold rules that ensure real estate prices remain affordable for the citizens .also the study recommends that future studies should be conducted to find out the relevant regulatory and policy issues that should be devel6ped and employed by regulatory policy makers in order to appropriately guided financial liberalization in the economy. Furthermore future studies could include more variables that affect real estate prices .also future studies should consider cross economy comparison